Long non-coding RNA CASC2 regulates cell biological behaviour through the MAPK signalling pathway in hepatocellular carcinoma. Issue 6 (May 2017) - Gan, Yuanyuan; Han, Nana; He, Xiaoqin; Yu, Jiajun; Zhang, Meixia; Zhou, Yujie; Liang, Huiling; Deng, Junjian; Zheng, Yongfa; Ge, Wei; Long, Zhixiong; Xu, Ximing
Long non-coding RNAs have previously been demonstrated to play important roles in regulating human diseases, especially cancer. However, the biological functions and molecular mechanisms of long non-coding RNAs in hepatocellular carcinoma have not been extensively studied. The long non-coding RNA CASC2 (cancer susceptibility candidate 2) has been characterised as a tumour suppressor in endometrial cancer and gliomas. However, the role and function of CASC2 in hepatocellular carcinoma remain unknown. In this study, using quantitative real-time polymerase chain reaction, we confirmed that CASC2 expression was downregulated in 50 hepatocellular carcinoma cases (62%) and in hepatocellular carcinoma cell lines compared with the paired adjacent tissues and normal liver cells. In vitro experiments further demonstrated that overexpressed CASC2 decreased hepatocellular carcinoma cell proliferation, migration and invasion as well as promoted apoptosis via inactivating the mitogen-activated protein kinase signalling pathway. Our findings demonstrate that CASC2 could be a useful tumour suppressor factor and a promising therapeutic target for hepatocellular carcinoma.